Program Digitalisasi Dorong Perekonomian Masyarakat Di Kelurahan Kampung Pondok, Kecamatan Padang Barat Kota Padang - Nofriadiman Nofriadiman; Veni Wedyawati; Eko Amri Jaya; Deri Kurniadi; Riko Ervil (Jurnal Kabar Masyarakat, 2023)
The model of electronic commerce (e-commerce) is developing very rapidly. In the business world, business people, especially online shop owners take this golden opportunity by making social media as one of the marketing media. Kampung Pondok Village is one of the centers of economic activity in Padang City, even West Sumatra. The majority of the people of Kelurahan Kampung Pondok are trades. One of the trade activities is the Kerupuk Jariang Rajo-Rajo. The Kerupuk Jariang Rajo-Rajo business has been in great demand by consumers even from neighboring countries and many other businesses are marketed manually through shop stores around the village of kampung cottage. The application of technology and information causes changes in new habits in the business field. The use of E-Commerce as a marketing medium that uses internet media is currently not difficult to reach by all circles. So that healthy and safe internet use needs to be instilled from an early age through learning healthy internet ethics in this Kampung Pondok district. socialization and introduction of how it is necessary to introduce good and appropriate internet use so as to make the people of Kampung Pondok Internet smart and able to marketing UMKM products on the Internet.